(3GdYedI h GdOhdI (B:s (3bQGAI aj OhQ GdYedI aj GdGbJUGO hGdSjGSI YHQ GdJGQjN GdbOje h GdhSjW (B/s - (3TfjJj,eMeO GdHTjQs ((3GdLRGFQ(B: s (3cfhR GdMceI(B, s, 2018)
(3GdGbJUGO GdWHjYj h GdOhdI bHd EHJcGQ GdYedI aj GdYGde GdbOje , GdJfXje GdSjGSj h GdGbJUGOj aj GdMVGQGJ GdeOfjI GdHGcQI eUQ GdbOjeI h HdGO GdQGaOjf, h GdJWQb Gdi GdJLGQI bHd GdYedI aj GdGbJUGOjGJ GdHGcQI , GdeHGOdGJ GdJLGQjI eOYGI GdYedI GdfbOjI , GdYedI GdfbOjI h GdSdWI GdSjGSjI , GdYedI GdfbOjI h GdJQhjL GdSjGSj, GdYedI GdfbOjI eWI ddOYGjI GdSjGSjI h GdYbGFOjI(B.s
(3eQGLY U(B.194 (3edGMb U(B.196s
Keywords: (3GdGbJUGOs; (3GdOhdIs; (3GdfbhOs